Sports selection in martial arts based on the harmonic stability of results at competitions - Nagovitsyn, R. S.; Zekrin, F. H.; Fendel, T. V.; Zubkov, D. A. (Journal of Human Sport & Exercise, 2019)
The aim of the study: to develop a new approach to sports selection in martial arts based on the analysis of the harmonic stability of the results of fighters in competitions during a sports career. Study participants: Greco-Roman wrestlers of different qualifications (n = 114). Research methods: based on the method of studying sports biographies of athletes, mathematical-statistical data processing was carried out using Student's t-criterion. The arithmetic average and harmonic average performance of each Greco-Roman style athlete of different qualifications. The smaller the deviation of the mean harmonic value from the arithmetic average performance of a fighter, the more stable his competitive result. The results of the study. As a result of the analysis, it was revealed that the higher the qualification of an athlete, the more reliable the non-significance of the difference in results between the arithmetic and average harmonic indices during a sports career is revealed. Findings. The proposed in the study a new approach to sports selection based on the analysis of the harmonic stability of the results of wrestlers at competitions allows to reliably identify the prospects of a wrestler.